2004
DOI: 10.1158/0008-5472.can-03-2614
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 Homeodomain Protein Suppresses the Growth of Prostate Cancer Cells by the Negative Regulation of T-Cell Factor 4

Abstract: In prostate gland, HOXB13 is highly expressed from the embryonic stages to adulthood. However, the function of HOXB13 in normal cell growth and tumorigenesis is not yet known. We investigated the role of HOXB13 and mechanism by which it functions in HOXB13-negative cells. Expression of HOXB13 was forced in HOXB13-negative PC3 prostate cancer cells using a liposome-mediated gene transfer approach. Compared with the control clones, HOXB13-expressing PC3 cells exhibited significant inhibition of in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 36 publications
5
97
1
Order By: Relevance
“…Thus far, studies pertaining to the growth modulatory role of HOXB13 in human tumors have been limited to prostate and renal cell carcinoma cell lines. Interestingly, the results of these studies, in contrast to our findings, suggest that HOXB13 plays a tumor suppressor role in the kidney and prostate (14,18,19). These contradictory findings are not necessarily surprising, because it is well known that the activity of HOX proteins depends on the cell in which the protein is acting (20).…”
Section: Knockdown Of Endogenous Hoxb13 In Human Ovarian Cancer Cellcontrasting
confidence: 99%
“…Thus far, studies pertaining to the growth modulatory role of HOXB13 in human tumors have been limited to prostate and renal cell carcinoma cell lines. Interestingly, the results of these studies, in contrast to our findings, suggest that HOXB13 plays a tumor suppressor role in the kidney and prostate (14,18,19). These contradictory findings are not necessarily surprising, because it is well known that the activity of HOX proteins depends on the cell in which the protein is acting (20).…”
Section: Knockdown Of Endogenous Hoxb13 In Human Ovarian Cancer Cellcontrasting
confidence: 99%
“…In addition, mice lacking Hoxb13 showed hypoplasia of the ventral prostate duct tips and did not produce secretory proteins, suggesting that Hoxb13 is required for the normal differentiation of the ventral prostate . A recent report also showed that ectopic expression of HOXB13 in a prostate cancer cell line induced G1 cell cycle arrest through negative regulation of T-cell factor-4, but did not lead to apoptotic change (Jung et al, 2004a). However, these reports did not mention the expression of HOXB13 in the kidney or renal tubular cells.…”
Section: Discussionmentioning
confidence: 98%
“…In human cutaneous malignant melanoma with distant metastasis, the expression level of certain HOX genes, including HOXB13, was higher than in those melanoma patients without metastases [23], and in endometrial cancer cells, antisense-transfection of the HOXB13 gene reduced the invasive ability of the cells [19]. In contrast, overexpression of HOXB13 in prostate cancer cells resulted in inhibition of cell growth and suppression of hormone-activated androgen receptor transcriptional activity, presumably via physical interaction with the receptor [24,25]. In the same study it was seen that estradiol-stimulated ER activity in breast cancer cells was not suppressed by HOXB13; in fact, if there was any influence on the activity it appears as though HOXB13 enhanced this activity [25].…”
Section: Discussionmentioning
confidence: 98%